Chapter L'approccio patrimoniale ai servizi ecosistemici - Granatiero, Gabriella (Territori, 2020)
The flourishing of literature on ecosystem services testifies to an increase in awareness of the extent to which economic operations of human societies is due to "natural" factors, so far considered as mere marginal conditions. However, this analysis appears to be flawed by an excessive of economism. It is limited to the evaluation of the effects and does not dive into the ecological relationships between community and environment. After introducing the concept of eco-territorial services, this section traces the coordinates of a more mature discussion of this topic, with important repercussions on land use planning.